2019
DOI: 10.3389/fonc.2019.00844
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Texture Analysis Based on PET/CT Images to Distinguish Hepatocellular Carcinoma and Hepatic Lymphoma

Abstract: Objectives: This study compared the diagnostic ability of image-based parameters with texture parameters in the differentiation of hepatocellular carcinoma (HCC) and hepatic lymphoma (HL) by positron emission tomography–computed tomography (PET/CT).Methods: Patients with pathological diagnosis of HCC and HL were included in this study. Image-based and texture parameters were obtained by manual drawing of region of interest. Receiver operating characteristic (ROC) was used to test the diagnostic capacity of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…We collected 47 publications on “Other” cancer types. This category included studies on gastrointestinal (11) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ], pancreatic (8) [ 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ], sarcoma (8) [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], neuroendocrine (5) [ 284 , 285 , 286 , 287 , 288 ], prostate (4) [ 289 , 290 , 291 , 292 ], thyroid (3) [ 293 , 294 , 295 ], thymic (2) [ 296 , 297 ], skin (2) [ 298 , 299 ], liver (2) [ 300 , 301 ], and renal carcinomas (1) [ 302 ]. The average number of patients was 84 (median = 70, range, 26–214) and the average number of textural features extracted was 29 (median = 17, ...…”
Section: Resultsmentioning
confidence: 99%
“…FDG-PET/CT scan was performed according to the European Association of Nuclear Medicine guidelines version 1.0 and, from February 2015, version 2.0. Steps of PET/CT scan were reported previously (24). Simple, circular regions-of-interest (ROIs) were drawn by hand on axial, coronal, or sagittal co-registered PET/CT slices.…”
Section: Imaging Studyingmentioning
confidence: 99%
“…Many studies have shown significant role of tumor heterogeneity evaluated from texture analysis in differentiating benign from malignant tumors, prediction of prognosis, response assessment in various tumors. [ 17 19 33 34 35 36 37 38 ] In the present study, IH based first-order mean, median, RMS, and GLCM-based second-order mean, autocorrelation, cluster prominence, cluster shade, sum average, sum variance were significant in the prediction of survival of NSCLC patients who underwent platinum-based chemotherapy. Among all these parameters, cluster prominence was the independent predictor of 1-year survival.…”
Section: Discussionmentioning
confidence: 48%